2017
DOI: 10.1002/ijc.30689
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA NEAT1 is a transcriptional target of p53 and modulates p53‐induced transactivation and tumor‐suppressor function

Abstract: p53 is one of the most important tumor suppressor genes, and the direct transcriptional targets of p53 must be explored to elucidate its functional mechanisms. Thus far, the p53 targets that have been primarily studied are protein-coding genes. Our previous study revealed that several long non-coding RNAs (lncRNAs) are direct transcriptional targets of p53, and knockdown of specific lncRNAs modulates p53-induced apoptosis. In this study, analysis of next-generation chromatin immunoprecipitation-sequencing (ChI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 23 publications
2
78
0
Order By: Relevance
“…Currently, accumulating lncRNAs have been identified in different biological processes, in which they act as critical regulators in both physiology and pathology, including tumorigenesis. Idogawa et al (26) reported that lncRNA NEAT1 was a transcriptional target of p53 and modulated p53-induced transactivation and tumor-suppressor function. Zhao et al (27) revealed that SNHG5/miR-32 axis regulated cell proliferation and migration of gastric cancer by targeting KLF4.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, accumulating lncRNAs have been identified in different biological processes, in which they act as critical regulators in both physiology and pathology, including tumorigenesis. Idogawa et al (26) reported that lncRNA NEAT1 was a transcriptional target of p53 and modulated p53-induced transactivation and tumor-suppressor function. Zhao et al (27) revealed that SNHG5/miR-32 axis regulated cell proliferation and migration of gastric cancer by targeting KLF4.…”
Section: Discussionmentioning
confidence: 99%
“…According to the site of lncRNA in the genome, it can be classified into 5 types: sense lncRNA, antisense lncRNA, bidirectional lncRNA, intronic lncRNA, and intergenic lncRNA [5]. The main functions of lncRNA include: (1) transcribing and interfering, (2) participating in chromosome rearrangement and histone modification, (3) modifying alternative splicing sequence, and (4) stabilizing mRNA [6]. lncRNA can regulate gene expression at the transcriptional level, post-transcriptional level, and epigenetic level, thus participating in the occurrence and development of tumors [7].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating documents have revealed that lncRNAs play a critical role in tumorigenesis and can be used as biomarkers for diagnosis or prediction of survival and recurrence in multiple cancers (5)(6)(7)(8)(9). For instance, in 2017, Idogawa et al reported that long non-coding RNA NEAT1 was a transcriptional target of p53 and modulated p53-induced transactivation and tumor-suppressor function (10). Zhou et al demonstrated that downregulation of lncRNA MEG3 mediated by DNMT3b contributed to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1α translation (11).…”
Section: Introductionmentioning
confidence: 99%